The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/ajh/hpt172
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension Does Not Increase Cardiovascular Risk in the Elderly at a Population Level

Abstract: Although OH seems to be a predictor of coronary, cerebrovascular, and HF events, no predictive role was found in models that include biological confounders. Independent of the cause of OH, age and systolic BP, which are positively associated with OH, fully explain the greater incidence of cardiovascular events and the greater cardiovascular risk observed in subjects with OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
2
16
0
2
Order By: Relevance
“…Eight studies reported data about the relationship between OH and heart failure . The pooled result demonstrated a positive relationship between OH and HF (summary HR 1.34, 95% CI 1.17‐1.52, P < 0.001), with moderate heterogeneity ( I 2 = 48.7%).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Eight studies reported data about the relationship between OH and heart failure . The pooled result demonstrated a positive relationship between OH and HF (summary HR 1.34, 95% CI 1.17‐1.52, P < 0.001), with moderate heterogeneity ( I 2 = 48.7%).…”
Section: Resultsmentioning
confidence: 95%
“…We chose the article written by Juraschek et al for its long follow‐up. Finally, 15 met the inclusion criteria and were included in the meta‐analysis . The majority of studies were performed in Europe, five were conducted in North America, and three were in Asia .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Extensive research has also tended (with some exceptions) to support a role for orthostatic hypotension as a risk factor for CVD in the elderly. [7][8][9] On the contrary orthostatic hypertension, has been less thoroughly analyzed. 10 It seems to affect about 10% of older people, but its reported prevalence varies because different criteria have been adopted to define it.…”
Section: Original Articlementioning
confidence: 99%